Knockdown of Pim-3 suppresses the tumorigenicity of glioblastoma by regulating cell cycle and apoptosis - Quan, J; Zhou, L; Qu, J (Cellular and Molecular Biology, 2015)
Products of the Pim (the proviral integration site for the Moloney murine leukemia virus) family of proto-oncogenes possess serine/threonine kinase activity and belong to the Ca2+/calmodulin-dependent protein kinase group. Pim-3, a member of the Pim family is closely linked to the development of a variety of tumors. However, the role of Pim-3 in human glioblastoma remains unknown. In this study, we elucidated the role of Pim-3 in the growth and apoptosis of glioblastoma cells. Western blotting was used for determination of protein levels, and shRNA was used for Pim-3 knockdown. The MTT assay was used to evaluate cell proliferation and flow cytometry was used to determine cell cycle status and the number of apoptotic cells. A mouse xenograft model was established by injecting nude mice with Pim-3-depleted glioblastoma cells in order to determine tumor growth in vivo. We demonstrated that Pim-3 was highly expressed in human glioblastoma cell lines. We also found that knockdown of Pim-3 by specific shRNA slowed decreased proliferation, induced cell cycle arrest in the G0/G1 phase, and increased apoptosis in glioblastoma cells. Pim-3 knockdown potently inhibited the growth of subcutaneously implanted glioblastoma cells in vivo. We further revealed that Pim-3 knockdown induced growth inhibition by reducing the levels of the anti-apoptotic protein Bcl-xl and cell cycle regulatory proteins, including cyclin D1 and Cdc25C, and increasing the levels of the pro-apoptotic protein Bax.